Acetone-Butanol-Ethanol as the Next Green Biofuel - A Review - Sri Mumpuni Ngesti Rahaju; Ibham Veza; Noreffendy Tamaldin; Ahmed Sule; Anthony C. Opia; Mohammed Bashir Abdulrahman; Djati Wibowo Djamari (Universitas Muhammadiyah Magelang, 2022)
The development of diesel engines faces challenging targets to satisfy stringent emissions regulation. To address this issue, the use of alcohol biofuels such as methanol and ethanol has attracted numerous attention due to their physicochemical properties and the possibility to be produced from renewable sources and agricultural waste material. Compared to ethanol, longer carbon alcohol such as butanol has higher energy density and lower latent heat, hygroscopicity, aggressivity, and toxicity. It can also be produced from biomass. Yet, despite its noticeable advantages, the use of butanol in the internal combustion engine is hindered by its low production efficiency. If Acetone-Butanol-Ethanol (ABE) is further distilled and purified, pure butanol and ethanol can be acquired, but this involves an energy-intensive process, thus increasing the production cost of butanol. To solve this problem, the direct use of ABE as a biofuel is considered a promising strategy. The idea of using ABE directly in internal combustion engines is then proposed to solve the economic issue of high butanol production costs. A scoping literature review was performed to screen and filter previously published papers on ABE by identifying knowledge gaps instead of discussing what is already known. Therefore, repeated and almost identical studies were eliminated, thus reporting only the most significant and impactful published papers. In terms of the objective, this article aims to review the progress of ABE as a promising biofuel in regard to the engine performance, combustion, and emission characteristics. Focus is also given to ABE’s physicochemical properties. Despite their considerable importance, the fuel properties of ABE are rarely discussed. Therefore, this review article intends to analytically discuss the physicochemical properties of ABE in terms of their calorific value, density, kinematic viscosity, and distillation. In general, it is concluded that engine emissions such as NOx and Particulate Matter (PM) could be reduced considerably with the use of ABE. Yet, the BSFC was found to increase due to the relatively lower calorific value and density of ABE blends as opposed to gasoline or diesel fuel, thereby increasing its fuel consumption. In terms of ABE’s fuel properties, in general, ABE can be used due to its satisfying physicochemical properties. However, it should be noted that the ABE-gasoline/diesel blends are greatly influenced by each of its component ratios (acetone, butanol, ethanol).